Analisis Potensi Produksi Sumber Bahan Pakan Lokal dan Kapasitas Tampung Ternak Ruminansia di Kabupaten Tanggamus - Muthoharoh, Septi (Wahana Peternakan, 2018)
This study aims to calculate the production potential of local feed material sources and the carrying capacity of ruminant livestock in Tanggamus Regency. The data source comes from the primary data and secondary data, then the collected data is analyzed descriptively. From the analysis it can be seen that forage feed material derived from grasses, agricultural products and plantations along with the waste that can be used for ruminant animal feed reaches 665,421.30 tons of dry matter per year. While from the available amount of feed, only 289,533.41 ton of dry material is used to fulfill feed requirement from 27,034.99 animal units, so the increasing capacity of ruminant livestock population can still be developed again up to 291,691.53 animal units, there is still the chance of adding as many as 264,656.54 animal units. Keywords: Carrying Capacity of Ruminant Livestock, Local Feed Material